SUGGESTIONS AND PRESCRIPTIONS FOR MAINTAINING GOOD HEALTH IN «REGIMEN SANITATIS SALERNI» BY ARNOLD OF VILLANOVA - Zahaiska, Halina M.; Petryshyn, Marta J.; Liubimova, Oxana V. (Aluna Publishing. Poland, 2022)
The aim: The aim of the study is collection, systematization and comprehensive analysis of suggestions and prescriptions for maintaining good health set forth by Arnold of Villanova in “Regimen Sanitatis Salerni”. Materials and methods: The research is based on the first edition of “The Salernitan Rule of Health” (1479) by Arnold of Villanova that comprises 364 poems (103 chapters). In this investigation we consciously leave some later editions of the “Rule” unattended since they contain insertions that do not belong to the author. Conclusions: Sanitary and hygiene suggestions, therapeutic practices, proper nutrition principles, analysis of influence of animal and plant products on the human body, prescriptions for medicinal plants administration are not merely a pathway to salubrity but also basic standards of sanitary and epidemic well-being. The medieval treatise has provided the underlying framework for modern dietology and healthy lifestyle.
The aim of the research is collection, systematization and comprehensive analysis of suggestions and prescriptions for maintaining good health set forth by Arnold of Villanova in “Regimen Sanitatis Salerni”.
Keywords: history of medicine, dietology, dietary pattern, hygiene